2006
DOI: 10.1038/sj.tpj.6500375
|View full text |Cite
|
Sign up to set email alerts
|

Discrete opioid gene expression impairment in the human fetal brain associated with maternal marijuana use

Abstract: Fetal development is a period sensitive to environmental influences such as maternal drug use. The most commonly used illicit drug by pregnant women is marijuana. The present study investigated the effects of in utero marijuana exposure on expression levels of opioid-related genes in the human fetal forebrain in light of the strong interaction between the cannabinoid and opioid systems. The study group consisted of 42 midgestation fetuses from saline-induced voluntary abortions. The opioid peptide precursors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 56 publications
0
56
0
Order By: Relevance
“…Using a multiple regression paradigm for confounding variables that included alcohol and cigarette use, prenatal marijuana exposure was shown to significantly alter opioid receptor expression in the mesolimbic forebrain: increased µ and κ receptor levels were found in the amygdala and mediodorsal thalamic nucleus, respectively (115). These observations are strengthened by prenatal THC (0.15 mg/kg, daily)-induced reduction of preproenkephalin mRNA expression in the rat nucleus accumbens (84) during early development.…”
Section: The Longitudinal Ottawa Prenatal Prospective Study (Opps) Anmentioning
confidence: 95%
“…Using a multiple regression paradigm for confounding variables that included alcohol and cigarette use, prenatal marijuana exposure was shown to significantly alter opioid receptor expression in the mesolimbic forebrain: increased µ and κ receptor levels were found in the amygdala and mediodorsal thalamic nucleus, respectively (115). These observations are strengthened by prenatal THC (0.15 mg/kg, daily)-induced reduction of preproenkephalin mRNA expression in the rat nucleus accumbens (84) during early development.…”
Section: The Longitudinal Ottawa Prenatal Prospective Study (Opps) Anmentioning
confidence: 95%
“…Pioneering studies from the Hurd laboratory have demonstrated increased heroin seeking in offspring prenatally exposed to THC 143,144 , trans-generational imprinting via epigenetic mechanisms through coincidently enhanced transcriptional repression and reduced transcriptional activation 34 , as well as misplacement of CB 1 R + hippocampal interneurons in neonatal offspring 93 . The neuronal basis for THC-induced drug-seeking behaviors in the offspring might be due to the altered neuropeptide (dynorphin, enkephalin) expression in mesocorticolimbic reward circuits 145 , and the erroneous synaptic wiring of glutamatergic cortical neurons 38 . Modifications to glutamatergic axons were shown to originate during neuronal development and be due to the CB 1 R-dependent degradation of SCG10/brain-specific stathmin-2, a determinant of microtubule elongation by sequestering tubulin dimers in a ternary T2S complex 146 .…”
Section: Cannabis Exposure During Pregnancymentioning
confidence: 99%
“…Of the developmental models, the prenatal condition has many challenges and multiple issues that must be considered that can signifi cantly impact the success of the experiment and interpretation of the data. Despite the apparent challenges, we have, for example, been able to document similar neurobiological changes in our prenatal rat model ( 39 ) to those seen in human fetuses with in utero cannabis exposure ( 54 ) . Such fi ndings support the validity of the animal models that can now be used to provide much-needed insight into the neurobiological mechanisms underlying developmental cannabis exposure that are highly related to neuropsychiatric disorders.…”
Section: Protocol: Rat Model Of Adolescent Cannabis Exposurementioning
confidence: 89%